Sosialisasi Dasar-Dasar Hukum Dan Mediasi Sebagai Alternatif Penyelesaian Sengketa Di Desa Purworejo Kecamatan Padang Ratu - Fristia Berdian Tamza; Ubaidah; Raju Pratama Sibuea; Lingga Putri Heriyani; Alfiani Nur Indah Sari (FT Universitas Lampung, 2025)
The Legal Fundamentals Socialization Program in Purwosari Village aims to enhance village officials' understanding of basic legal principles and the concept of mediation as an alternative for more effective dispute resolution. This study employs a qualitative descriptive method using observation, interviews, and document analysis. The socialization process includes delivering legal and mediation materials, interactive discussions, mediation simulations, and providing supporting materials. The results indicate that this program successfully increased the legal awareness of village officials and equipped them with skills to resolve conflicts peacefully. Through this program, village officials are expected to become wise mediators, create a more harmonious environment, and improve transparency and accountability in village governance.